The impacts of water level fluctuations from paddy fields and aquaculture ponds on wetland habitats for wintering waterbirds: Implications for wetland management - Cheng, Bo; Zhu, Xiudi; Alatalo, Juha M.; Gordon, Jessica; Li, Hongqing; Jiang, Bo; Yin, Wei (Frontiers in Environmental Science, 2022)
The distribution and composition of wetland habitats for wintering waterbirds are heavily influenced by water level fluctuations. Through polder construction and aquaculture activities, paddy fields and aquaculture ponds have decreased the lateral connectivity of water level fluctuations in the natural state of the lake. However, the impacts of water level fluctuations on habitat suitability, which can be seen using high-resolution images analysis, often cannot separate disturbances caused by the paddy fields and aquaculture ponds, and it is difficult to capture the actual impact of water level fluctuations from the operation of water conservancy projects on wetland habitats. Based on remote sensing image data and hydrological data, this paper selected Caizi Lake as a study site and comparatively analyzed the changes in wintering waterbird habitats in a water level sequence under the two scenarios. Our work showed that remote sensing image analysis usually exaggerates the impacts of water level fluctuations casued by the operation of water conservancy projects on wetland habitats. Additionally, paddy fields and aquaculture ponds should be considered as potential options for creating more suitable habitats for migratory waterbirds if combined with reasonable and effective regulation of the water level within the paddy fields and aquaculture ponds. The present study results could facilitate the management and sustainable utilization of Caizi Lake wetlands and provide support for creating small habitats by regulating the water levels of paddy fields and aquaculture ponds through the Yangtze-to-Huaihe Water Diversion (YHWD) Project.